The Conception of Citizen Knowledge in Democratic Theory - Rapeli, Lauri; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
What according to democratic theorists should the ordinary citizen know about politics? What does several decades of empirical research about citizens' political knowledge tell us? And why should we care? This book offers a comprehensive outline of the vast literature on political knowledge and by providing an analytical framework for its studying.
Keywords: Science; Science; Science, general